Respuesta :
Answer:
D. slope = 3 and y-intercept = -3
Step-by-step explanation:
The equation can be rearranged by adding the opposite of the term with parentheses:
y = 3(x -1)
Expanding this to slope-intercept form gives ...
y = 3x -3 . . . . . . . . slope = 3, y-intercept = -3
_____
Slope-intercept form is ...
y = mx +b . . . . . . . . slope = m, y-intercept = b
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/d94/1e19bcad36f52494a2bbcbe74fb1ed9f.png)
Answer:
the correct answer would be D.
Step-by-step explanation: